Using ensemble modeling to predict the impacts of assisted migration on recipient ecosystems. Issue 2 (2nd September 2020) - Peterson, Katie; Bode, Michael
Abstract: Assisted migration is a controversial conservation measure that aims to protect threatened species by moving part of their population outside its natural range. Although this could save species from extinction, it also introduces a range of risks. The magnitude of the threat to recipient ecosystems has not been investigated quantitatively, despite being the most common criticism leveled at the action. We used an ensemble modeling framework to estimate the risks of assisted migration to existing species within ecosystems. With this approach, we calculated the consequences of an assisted migration project across a very large combination of translocated species and recipient ecosystems. We predicted the probability of a successful assisted migration and the number of local extinctions would result from establishment of the translocated species. Using an ensemble of 1.5 × 10 6 simulated 15‐species recipient ecosystems, we estimated that translocated species will successfully establish in 83% of cases if introduced to stable, high‐quality habitats. However, assisted migration projects were estimated to cause an average of 0.6 extinctions and 5% of successful translocations triggered 4 or more local extinctions. Quantifying the impacts to species within recipient ecosystems is critical to help managers weigh the benefits and negative consequences of assisted migration. Abstract : Article Impact Statement : Assisted migration is controversial conservation initiative because its effects on recipient ecosystems are not easily predicted. Abstract : Modelación en Conjunto para Predecir los Impactos de la Migración Asistida sobre los Ecosistemas Receptores Resumen: La migración asistida es una medida controversial de conservación que busca proteger a las especies amenazadas mediante la mudanza de parte de su población fuera de su extensión natural. Este método podría salvar a las especies de la extinción, pero también implica una gama de riesgos. La magnitud de la amenaza para el ecosistema receptor no ha sido investigada cuantitativamente a pesar de ser la crítica más común para esta acción. Usamos un marco de trabajo de modelación en conjunto para estimar los riesgos de la migración asistida para las especies existentes dentro de los ecosistemas. Mediante este enfoque calculamos las consecuencias de un proyecto de migración asistida en una combinación de especies reubicadas y ecosistemas receptores. Pronosticamos la probabilidad de una migración asistida exitosa y el número local de extinciones que resultarían de la introducción de especies reubicadas. Con un conjunto simulado de 1.5 × 10 6 ecosistemas receptores con 15 especies, estimamos que las especies reubicadas se establecerán exitosamente en 83% de los casos si son introducidas a hábitats estables y de alta calidad. Sin embargo, se estimó que los proyectos de migración asistida causarían un promedio de 0.6 extinciones y el 5% de las reubicaciones exitosas generaron cuatro o más extinciones locales. La cuantificación de los impactos para las especies dentro de los ecosistemas receptores es crítica para ayudar a los manejadores a sopesar los beneficios y las consecuencias negativas de la migración asistida. 摘要: 辅助迁移旨在将濒危物种的部分种群移出其自然分布范围来对其进行保护, 是一项有争议的保护措施。这种做法虽然有可能使物种免于灭绝, 但也带来了一系列风险。然而, 这种行动对接纳迁移物种的生态系统的威胁程度还没有得到定量研究, 这也是针对该行动最常见的批评。本研究使用整体建模框架估计了生态系统现有物种面临辅助迁移的风险, 并计算了一系列被迁移物种与迁入地生态系统组合的辅助迁移项目的结果。我们还预测了辅助迁移成功的可能性, 以及迁移物种建群导致当地物种灭绝的数量。利用 15 个物种与迁入地生态系统共 1.5 × 10 6 种模拟的数据集, 我们估计, 如果迁移物种被引入到稳定的高质量栖息地, 将有 83% 的情况能够成功建立种群。然而, 估计结果还显示, 辅助迁移项目平均会造成 0.6 次物种灭绝, 5% 的成功迁移还会引发了4次或以上的当地物种灭绝。量化迁入地生态系统中物种受到的影响, 对于帮助管理者权衡辅助迁移的利弊至关重要。【翻译: 胡怡思; 审校: 聂永刚】